AS RELAÇÕES INTERPESSOAIS NA SALA DE AULA E A BRINQUEDOTECA ESCOLAR - Deise Caroline Rodrigues da Silva; Andréia Cristiane Silva Wiezzel (Universidade do Oeste Paulista, 2011)
This work comes to present the partial results of a research and extension project called Interpersonal Relations and Contributions at the Dynamic Classroom, conducted by students and teachers in the FCTUNESP at Presidente Prudente - São Paulo. The project involved studying interpersonal relationships among children attending kindergarten in a public school in the county. Aspects related to excessive timidity and aggression are investigated by researchers, who accompany the children in toy/play activities in school. The project seeks also to investigate the aggressiveness and shyness, to provide grants to teachers and parents on how they deal with childrens conflicts and also help children relate better within the school environment.